Centralised ESG Data Sharing and EU Competition Law: Safeguards for the Twin Transition - Mariska van de Sanden; Pim Jansen (European Journal of Risk Regulation)
Over the past decade the European Union (EU) has transformed sustainability into a dense matrix of legally binding ESG reporting obligations for companies. Compliance increasingly hinges on firms’ ability to collect and verify thousands of datapoints deep into global supply chains – an exercise that is costly, error-prone and may yield non-comparable results. (Semi-)centralised ESG data-sharing arrangements – shared hubs where suppliers post one or more verified sets of sustainability figures that all their customers can reuse – can restore some efficiency by eliminating duplicate requests and supplying standardised, audit-ready inputs, but this amplifies competition-law risk. Drawing on competition law and policy and recent Dutch banking practice, the paper devises a set of legal “firewalls” and access rules that neutralise collusive potential resulting from the information exchange that takes place while safeguarding smaller market players from exclusion. These safeguards are essential to ensure that ESG data collaboration supports – not hinders – the EU’s Twin Transition towards a green and digital economy.